Physical Exercise Potentially Targets Epicardial Adipose Tissue to Reduce Cardiovascular Disease Risk in Patients with Metabolic Diseases: Oxidative Stress and Inflammation Emerge as Major Therapeutic Targets - Thembeka A. Nyawo; Carmen Pheiffer; Sithandiwe E. Mazibuko-Mbeje; Sinenhlanhla X. H. Mthembu; Tawanda M. Nyambuya; Bongani B. Nkambule; Hanél Sadie-Van Gijsen; Hans Strijdom; Luca Tiano; Phiwayinkosi V. Dludla (MDPI AG, 2021)
Excess epicardial adiposity, within a state of obesity and metabolic syndrome, is emerging as an important risk factor for the development of cardiovascular diseases (CVDs). Accordingly, increased epicardial fat thickness (EFT) implicates the exacerbation of pathological mechanisms involving oxidative stress and inflammation within the heart, which may accelerate the development of CVDs. This explains increased interest in targeting EFT reduction to attenuate the detrimental effects of oxidative stress and inflammation within the setting of metabolic syndrome. Here, we critically discuss clinical and preclinical evidence on the impact of physical exercise on EFT in correlation with reduced CVD risk within a setting of metabolic disease. This review also brings a unique perspective on the implications of oxidative stress and inflammation as major pathological consequences that link increased EFT to accelerated CVD risk in conditions of metabolic disease.